2015
DOI: 10.1080/15384101.2015.1049783
|View full text |Cite
|
Sign up to set email alerts
|

p53 checkpoint ablation exacerbates the phenotype of Hinfp dependent histone H4 deficiency

Abstract: Histone Nuclear Factor P (HINFP) is essential for expression of histone H4 genes. Ablation of Hinfp and consequential depletion of histones alter nucleosome spacing and cause stalled replication and DNA damage that ultimately result in genomic instability. Faithful replication and packaging of newly replicated DNA are required for normal cell cycle control and proliferation. The tumor suppressor protein p53, the guardian of the genome, controls multiple cell cycle checkpoints and its loss leads to cellular tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…80 Similarly, depletion of HiNF-P from cultured cells results in a dispersion of HLBs into smaller bodies, although they still form. 81,82 These data indicate that HiNF-P is not required for mammalian HLB formation but may promote complete HLB assembly via its role in H4 transcription.…”
Section: Self-organization Of the Hlbmentioning
confidence: 92%
“…80 Similarly, depletion of HiNF-P from cultured cells results in a dispersion of HLBs into smaller bodies, although they still form. 81,82 These data indicate that HiNF-P is not required for mammalian HLB formation but may promote complete HLB assembly via its role in H4 transcription.…”
Section: Self-organization Of the Hlbmentioning
confidence: 92%
“…Deregulation of histone gene expression upon loss of HINFP or NPAT causes disruption of HLBs and has drastic consequences for cell division and cell survival in both normal and cancer cells (Di Fruscio et al, ; Ghule et al, , ; Ma et al, ). The resulting changes in the organization of newly replicated chromatin create both genomic instability and chromosomal aberrations, that are frequently observed during tumorigenesis.…”
Section: Histone Gene Expression In Nuclear Microenvironmentsmentioning
confidence: 99%
“…Recently it was demonstrated that Hinfp‐mediated deregulation of histone H4 results in cellular and molecular defects that lead to genomic instability. Functional evidence has been provided that the tight coupling between DNA replication and histone synthesis is reciprocal (Ghule et al, ) Furthermore, simultaneous loss of Hinfp and p53 exacerbates cellular defects (Ghule et al, ). We observed that siRNA‐depletion of HINFP‐regulated H4 mRNAs causes genomic instability (unpublished data).…”
Section: Hinfp Is An Essential Regulator Of Histone Gene Transcriptiomentioning
confidence: 99%
“…Loss of Hinfp causes replicative stress and DNA damage (Ghule et al, 2014) and simultaneous loss of the tumor suppressor protein p53 exacerbates proliferative defects in cell culture models (Ghule et al, 2015). Therefore, we investigated whether loss of Hinfp provokes DNA damage in E3.5 stage embryos using accumulation of phospho-H2AX (Ser-139) foci as a marker for double-stranded DNA breaks.…”
Section: Resultsmentioning
confidence: 99%
“…The immediate cellular consequences of H4 deficiency are structural changes in chromatin organization that predispose to DNA damage and aneuploidy (Ghule et al, 2015; Ghule et al, 2014). These genomic changes ultimately generate cell cycle arrest and/or cell death.…”
Section: Discussionmentioning
confidence: 99%